The Mediating Effect of Student Understanding in Filipino Subject in the Relationship Between Learning Experience and Communicative Skills - Egar, Rowena; Oliva, Elleine Rose (Journal of Natural Language and Linguistics, 2024)
This research aims to investigate the mediating effect of students’ level of understanding in Filipino in the relationship between learning experiences and communicative skills. This is a non-experimental quantitative study that employed correlation and mediation research design. Data were collected through a face-to-face survey of 465 students at a public secondary school in the division of Bukidnon. Respondents were selected using stratified ramdom sampling. The statistical tools used were mean, Pearson r, and Medgraph Sobel z-test, utilizing a validated, adapted, and modified questionnaire. The findings revealed that learning experiences scored a high level, as did the dependent variable, communicative skills, and the mediating variable, students’ understanding of Filipino subjects. It was also found that there is a significant relationship between learning experiences and communicative skills, learning experiences and students’ understanding in Filipino, and students’ understanding and communicative skills. It was found that students’ understanding of Filipino has a partial mediating effect on the relationship between students’ learning experiences and communicative skills. Hence, there should be a focus on developing communicative skills at present for meaningful learning using the language in the social context.